Analisis Keterkaitan Sektoral dan Spasial Provinsi Banten dalam Perspektif Interregional Input-Output - Saeful Hidayat (Jurnal Ekonomi-Qu, 2022)
Banten has an important role in the Indonesian economy. However, the high import of raw materials from abroad indicates that Banten's economy is less related to the production sector inside and outside Banten. Meanwhile, these linkages are needed to accelerate economic development and increase Banten's role in the national economy. This study aims to analyze the interrelationships between economic sectors in the Banten economy and spatial linkages with other provinces in Indonesia. The analysis is carried out through forward linkage and backward linkage analysis, interregional spillover effects, and interregional feedback effects, using the IRIO Indonesia Table 2016. The results show that the Banten economy is not optimal in utilizing domestic industries as suppliers of raw materials. As a result, when Banten experienced an increase in final consumption, it was less able to improve the performance of the domestic and national upstream economic sectors. Conversely, if in other provinces there is an increase in final demand, Banten will receive a very large impact because it has used the production sector in other provinces as a market for its products. As a result, when the Banten production sector experienced an increase in production due to increased production capacity, it was able to improve the performance of the downstream economic sector in the country.